2002
DOI: 10.1136/jcp.55.10.754
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the prevalence of undiagnosed coeliac disease in laboratory defined iron and folate deficiency

Abstract: Aims: To determine the prevalence of coeliac disease in a group of patients in the community who have been shown in the laboratory to have iron and/or folate deficiency. To assess the cost efficiency of this laboratory based case finding strategy. Methods: The study was undertaken in a large general hospital in the UK serving a population of 300 000. Three hundred and thirty three eligible patients with iron and/or folate deficiency were identified and contacted over an 18 month period. Case finding was by tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
58
0
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 12 publications
1
58
0
6
Order By: Relevance
“…Anemia, especially IDA, is a frequent feature in CD and may be the only presenting symptom (2). Increased prevalence of CD has been found in patients with IDA (16,17). An early identification of CD in patients with IDA has great importance, since a strict adherence to a gluten-free diet not only provides management of anemia but also prevents the severe complications such as ulcerative jejunoileitis, intestinal lymphoma and neoplasm (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anemia, especially IDA, is a frequent feature in CD and may be the only presenting symptom (2). Increased prevalence of CD has been found in patients with IDA (16,17). An early identification of CD in patients with IDA has great importance, since a strict adherence to a gluten-free diet not only provides management of anemia but also prevents the severe complications such as ulcerative jejunoileitis, intestinal lymphoma and neoplasm (20).…”
Section: Discussionmentioning
confidence: 99%
“…Only a minority of CD patients present with classical malabsorption symptoms, whereas most patients have subclinical or silent forms in which IDA can be the sole presentation (15). The prevalence of CD was found between 4.7-5% in patients with IDA (16,17).…”
mentioning
confidence: 99%
“…In a study by Unsworth et al prevalence of celiac disease in anemic children was reported 6.6% [20] .Similarly in another study by Howard et al ,the prevalence of Celiac disease in anemic patient was found 10.9% while Annibale et al reported 13.7% prevalence of Celiac disease in anemic children [21], [22]. In another study by Grisolano et al, 103 anemic patients were screened by duodenal biopsy and 8.7% were found positive on biopsy [15] .…”
Section: Discussionmentioning
confidence: 93%
“…Çoğu hastada, endoskopik olarak duodenumda başta mukozal kıvrımlarda azalma, daha az duyarlılıkla da mozaik patern, nodülarite ve tarak şeklinde [6]. Ancak bunlar içerisinde iki çalışmada pozitif seroloji ve duoneal biyopsi ile kanıtlanmış çölyak hastalığı prevalansı % 2,3 ve % 4,7 olarak bildirilmiştir [7,8]. Bizim çalışmamızda da bu literatürler ile uyumlu olarak sadece 1 hastada (% 4,5) tipik semptom ve birlikte vitamin B12 veya folat eksikliği olmadan sadece demir eksikliği anemisi nedeniyle araştırılırken çölyak hastalığı tanısı konulduğu tespit edildi.…”
Section: Discussionunclassified